Mortality Predictors among COVID-19 Patients Admitted to the Intensive Care Unit in Sulaymaniyah City, Iraq: A Cross-Sectional Study - Alyaa Amer Abdulla; Sherzad Ali Ismael (Advanced Medical Journal)
Background and objectives: On February 22, 2020, Iraq confirmed the first case of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The number of confirmed cases in Sulaimaniyah city reached 152,846, with 3,178 deaths. Our objective was to assess the clinical characteristics and identify variables that may predict mortality of COVID-19 cases in the intensive care unit.